Antioxidant Activity of Flavonoid from Rhizome Kaemferia galanga L. Extract - Hayati, Elok Kamilah; Ningsih, Rachmawati; Latifah, Latifah (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
Kaemferia galanga L. rhizome is a traditional crop which is widely used for herbal medicine.Â This research is started from the extraction of maceration using ethanol 80% and partition with chloroform:water. 80 % ethanol extract and chloroform fraction tested antioxidant activity with DPPH (1,1-diphenyl-2-picrylhydrazyl), phytochemicals with reagents, separation of the active compound by TLC (thin layer chromatography) analytical and preparative TLC, the identification of compounds with sliding reagent using UV-Vis. The test results on the antioxidant activity of 80% ethanol extract of 64,93% (100 ppm) and chloroform fraction of 54,9 % (100 ppm) with indigo IC50 of 13,07 mg/mL and 81,9 mg mL. 80 % ethanol extract and chloroform fraction has potential as a source of natural antioxidants. Phytochemical test showed 80% ethanol extract contains flavonoids, alkaloids and tannins. At the chloroform fraction extract containing flavonoids. The separation of the active compounds with analytical TLC using eluent PE: ethyl acetate (5: 1) resulted in 7 stain (Rf 0,06 to 0,96) and preparative TLC produce 8 spots (Rf from 0,19 to 0,83). Results from UV-Vis spectrum can be presumed that such a class of flavonoid compounds flavanones or dihidroflavonol. It can be seen from the wavelength range 210-285 nm in the bands I and 300-550 nm in band II. The addition of the reagent slide showed the presence of hydroxyl groups in ring A, B and C and O-hydroxy on ring A.Â Keywords: antioxidant activity, Kaemferia galanga rizhome, sliding reagent, Thin Layer Chromatography, 1,1-diphenyl-2-picrylhydrazylÂ